(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
Soybean oil and palm oil are the most preferred vegetable oils in the world. The aim of the study was the correlative and qualitative appraisement of the edible vegetable oils available in Bangladesh. Five brands of soybean and one brand of palm oil were comparatively assessed to select which one was better for edible purpose. In this study the quality of the edible oils was analyzed by evaluating some physicochemical attributes such as specific gravity, color and odor, moisture content, acid value, saponification value, iodine value and peroxide value using standard methods. A significant difference (P<0.05) was found in all characteristic parameters of different oil samples. The study expressed the following properties as ranged values for soybean oils and single value for palm oil: Iodine value (82.34±0.633 –108.63±0.96 g I2/100 g; 45.68±0.604 g I2/100 g), Saponification value (182.33±2.670–197.39±1.987 mg KOH/g; 203.68±2.346 mg KOH/g), Acid value (0.33±0.06–0.57±0.03 mg KOH/g; 1.07±0.07 mg KOH/g), Peroxide value (1.13±0.01–1.96±0.006 meq O2/kg; 1.09±0.02 meq O2/kg), Moisture content (0.30±0.005–0.63±0.026%; 0.65±0.015%), specific gravity (0.88±0.15–0.94±0.07 g/ml; 0.91±0.03 g/ml). Taking consideration of all parameters the study concluded that Rupchanda and Fresh soybean oil had superior quality than other samples. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 156-161